"It is impossible to teach English in English": Preservice teachers' struggles to facilitate L2 comprehensibility in English. Issue 2 (2nd February 2021) - Barahona, Malba; Delaporte‐Raurich, Catalina; Ibaceta‐Quijanes, Ximena
Abstract : Teachers' use of the target language for instruction in the context of foreign language teaching has been identified as a key factor for learning. However, it has also been observed that teachers do not use the target language for reasons such as lack of proficiency in the second language (L2), lack of pedagogical content knowledge or confidence in that knowledge, doubt that their students will understand, and specific cultural practices. This article reports on a study that investigated the implementation of a university‐based classroom intervention centered on a practice‐based approach in an initial English language teacher education program in Chile. This intervention aimed at understanding how a group of preservice teachers learned how to enact strategies to facilitate L2 comprehensibility in English. Findings demonstrate that a practice‐based approach can provide effective opportunities for preservice teachers to develop pedagogical content knowledge and become more confident in using English more effectively in their lessons. Findings also reveal that preservice teachers struggled in this process; however, they tended to develop higher levels of reflection as they learned how to facilitate L2. The article concludes with a discussion about key reasons preservice teachers claimed for using the first language in English lessons.